Pengembangan Kajian Ekonomi Pertahanan di Indonesia Melalui Studi Narasi Arkeologi dan Filologi Terkait Kerajaan Mataram - Endro Tri Susdarwono (Program Studi Pendidikan Sejarah Universitas Riau, 2022)
This study is part of the study of narrative psychology, a science that studies how historical stories shape the influence of current human behavior if and someone's personality shapes their lives. The role of inherited manuscripts for storing information about life in the past, for the present life gave birth to the need for maintenance and utilization. In a number of the manuscripts described it can be understood that there is a content that turns out to be used in the development of studies in the realm of defense economics. Research and development of archeology so far has produced data that can be divided chronologically into three (3) periods, namely the Prehistoric, Classical (Hindhu-Buddhist) period, and the Islamic and Colonial periods. Each period is divided into several aspects of research. The results of archeology research and development can be utilized for the public interest, especially those related to the past reconstruction of values ​​which are very useful for human life now and for generations to come. Archeological research and development can be used to develop defense economy studies that are in accordance with the character and identity of the Indonesian people. Defense economics continues to develop as a reflection of the problem of allocation of resources and of course each country has its own perspective on facing the challenges of defense economic issues. In general, the dissemination of economic studies on defense can be approached from when a large conflict occurs. The contemporary defense economy is more interested in working on those related to conventional, ethnic and conflict wars including revolutions, civil wars and long wars.